VARIATION IN GLYCOGEN OF GLOSSOGOBIUS GIURIS (HAMILTON). FROM SADATPUR LAKE IN RELATION TO SEX AND MATURITY - PAWAR, B. A.; MANE, U. H.; AHER, S. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2018)
Variation in glycogen content in the gonads, liver and muscles of Glossogobius giuris from Sadatpur lake near Pravaranagar found to be influenced by breeding cycle and feeding intensity. During maturation the glycogen contents increased in the gonads and liver while decreased in the muscles. In the muscles, glycogen content increase during spent condition indicates high feeding intensity. In general the glycogen content was more in the gonads, liver and muscles of females as compared to males.